2011
DOI: 10.1111/j.1553-2712.2011.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

More Patients Are Triaged Using the Emergency Severity Index Than Any Other Triage Acuity System in the United States

Abstract: Objectives: Patient acuity triage systems can play an important role in supporting patient safety and emergency department (ED) operations. In 2003, the boards of the American College of Emergency Physicians (ACEP) and the Emergency Nurses Association (ENA) approved a joint statement calling for hospitals to adopt a reliable, valid, five-level triage scale such as the Emergency Severity Index (ESI). Still, there appears to be considerable variation in use of triage acuity systems in the United States, with man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 7 publications
0
90
0
1
Order By: Relevance
“…Le triage en structure des urgences (SU) a fait l'objet de recommandations en 2012 sous l'Ă©gide de la SociĂ©tĂ© française de mĂ©decine d'urgence [1]. Bien que des Ă©chelles de triage Ă  trois niveaux soient encore utilisĂ©es [2], les Ă©chelles Ă  cinq niveaux comme la classification infirmiĂšre des malades aux urgences (CIMU) semblent supĂ©rieures en termes de reproductibilitĂ© et d'exactitude [3][4][5].…”
unclassified
“…Le triage en structure des urgences (SU) a fait l'objet de recommandations en 2012 sous l'Ă©gide de la SociĂ©tĂ© française de mĂ©decine d'urgence [1]. Bien que des Ă©chelles de triage Ă  trois niveaux soient encore utilisĂ©es [2], les Ă©chelles Ă  cinq niveaux comme la classification infirmiĂšre des malades aux urgences (CIMU) semblent supĂ©rieures en termes de reproductibilitĂ© et d'exactitude [3][4][5].…”
unclassified
“…[8] It is the most widely used triage system in the United States and is becoming more widely used in other non English speaking countries. [9,10] There are many other five level ED triage systems used worldwide including the Manchester Triage System (MTS), the Canadian Triage and Acuity Scale (CTAS), the Australasian Triage Scale (ATS), among other multi level informal systems. [5,[11][12][13] In both the ATS and CTAS system, each level has a time goal to initiation of medical evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] A survey carried out in US in 4897 hospitals showed that there is no triage system in 0.7% of emergency departments, a 2-level triage system in 0.3%, a 3-level triage system in 25.2%, a 4-level triage system in 9.6%, a 5-level ESI triage system in 56.9%, another 5-level triage system in 6.3%, and other triage system in 0.1% of emergency departments. [20] It was also shown that the triage level application has changed according to the number of incoming patients; while 5-level ESI triage system applied in 78.3% of crowded emergency departments having more than 100.000 or more annual urgent patients, 3-level triage system has been applied in 60.2% of the emergency departments having less than 1.000 annual urgent patients. [20,21] As suggested in the statement published in 2009 by the Ministry of Health of Turkish Government, the 3-level triage system has been commonly used in Turkey.…”
mentioning
confidence: 99%
“…[20] It was also shown that the triage level application has changed according to the number of incoming patients; while 5-level ESI triage system applied in 78.3% of crowded emergency departments having more than 100.000 or more annual urgent patients, 3-level triage system has been applied in 60.2% of the emergency departments having less than 1.000 annual urgent patients. [20,21] As suggested in the statement published in 2009 by the Ministry of Health of Turkish Government, the 3-level triage system has been commonly used in Turkey. In 3-level triage system, patients are categorized as emergent (red), urgent (yellow) and non-urgent (green).…”
mentioning
confidence: 99%